Malondialdehyde as a marker of oxidative stress in periodontitis patients - Deepthi A Cherian; Tim Peter; Anjhana Narayanan; Sanupa S Madhavan; Sylvana Achammada; Gopinath Parakkat Vynat (Wolters Kluwer Medknow Publications, 2019)
Background: Periodontology is a fast-evolving field with newer insights into traditional periodontal diagnosis. Advances in periodontal disease diagnostic research are moving toward methods whereby periodontal risk can be identified and quantified by objective measures such as biomarkers. Objectives: The aim of this study was to evaluate malondialdehyde (MDA) levels in whole saliva of patients with chronic periodontitis. Materials and Methods: Whole saliva samples were collected from 85 patients: 30 patients with chronic periodontitis, 25 with gingivitis, and 30 periodontally healthy controls. To determine the clinical condition of each subject, the gingival index and clinical attachment level were measured. The salivary MDA levels were determined spectrophotometrically. Results: Higher salivary MDA levels (P < 0.005) were detected in patients with periodontitis compared to the healthy controls. There was no statistically significant difference in the salivary MDA levels between patients with gingivitis and healthy controls. Conclusions: Higher salivary MDA levels seem to reflect increased oxygen radical activity during periodontal inflammation. Thus, MDA can be used as a marker of oxidative stress in patients with periodontitis.